Arctic deep-sea benthos: biodiversity, biological traits, and food webs - Zhulay, Irina (UiT The Arctic University of Norway, 2022)
Understanding Arctic deep-sea ecosystem structure and functioning is an urgent task because ongoing sea-ice reduction modifies and opens up these regions for resource exploitation. This thesis aims to increase knowledge on epibenthos in the Chukchi Borderland (deep Arctic Ocean). Paper I documents low epifaunal densities and biomass, a total of 152 taxa, and dominance of Echinodermata, Arthropoda and Cnidaria for taxon richness and/or abundance/biomass. Most taxa had Atlantic biogeographic affinity. Ridge and plateau community structure did not differ but western and eastern communities did, linked to food input and drop-stone availability. Paper II findings generally support the current view of common trait modalities in deep-sea epibenthos. Higher functional diversity at mid-depth than deep stations indicated more variable resource use, while higher functional redundancy in basin communities suggested adaptation to more homogeneous environments by fewer, shared traits. Paper III suggests tighter pelagic-benthic coupling in 2005 (high sea-ice cover) than 2016 (low sea-ice cover), reflected in higher isotopic-niche overlap and shorter isotopic-distances between pelagic and benthic systems in 2005. Isotope values suggest higher ice algal contribution in 2005 and more refractory food consumed by benthos in 2016. This study adds much-needed biological and ecological knowledge with implications for vulnerability and resilience and highlights the need for deep-sea monitoring.